Exploring Learner Engagement with English Debates: A Case Study of Chinese University Students - Yang, Ruiyu (Transactions on Social Science, Education and Humanities Research, 2024)
While many studies have examined students’ participation in English debates with a focus on their development of English argumentation skills, second language (L2) learners’ engagement with English debates has yet to be explored. Informed by a tripartite model on learner engagement, this study employed a case study involving four Chinese L2 learners to explore how they cognitively, behaviourally, and affectively engaged with English debates. Data was collected from multiple sources, including semi-structured interviews with students, notes taken in the debate classes, and class observations. Iterative analysis of the data revealed different patterns of learner engagement at all three dimensions among the four participants. It was also found that multiple factors, including their understanding of argumentation skills, self-evaluation of their language proficiency, their learning attitudes, and the instructor’s teaching methods, played a role in their engagement with English debates. The findings suggest that teachers need to consider individual students’ attitudes, beliefs, and L2 proficiency and provide explicit instruction on argumentation skills to enhance their engagement with English debate.